Effects of Melatonin Priming on Suaeda corniculata Seed Germination, Antioxidant Defense, and Reserve Mobilization: Implications for Salinized Wetland Restoration - Zhang, Mingye; Liu, Shuchen; Tong, Shouzheng; Zhang, Dongjie; Qi, Qing; Wang, Yanji; Wang, Xuehong; An, Yu; Lu, Xianguo (Frontiers in Ecology and Evolution, 2022)
Melatonin priming has been widely reported to positively affect seed germination under abiotic stresses. However, there is still a gap in knowledge on how melatonin priming impacts the seed germination and physiological change of wetland plant species. We assessed the effects of different melatonin concentrations on germination characteristics, antioxidant defense, and reserve mobilization of Suaeda corniculata seeds. Priming of S. corniculata seeds with 50 μM melatonin significantly improved the germination rate, germination speed, germination index, superoxide dismutase and peroxidase activity, and soluble sugar content as compared with the control, and effectively reduced the malondialdehyde content, promoted starch, soluble protein, and fat mobilization. However, the stress tolerance ability of S. corniculata seeds was reduced by high melatonin concentration. The structural equation model indicated that the melatonin priming directly affects the seed germination, while also indirectly regulating the antioxidant defense system and reserve mobilization. In conclusion, melatonin priming affects the S. corniculata seed germination under salinization stress in a concentration-dependent manner via both direct and indirect regulatory pathways. Insights into these aspects will advance our understanding of how melatonin priming affects S. corniculata seed germination and provide invaluable information and technical support for the restoration of salinized wetlands in the Momoge Nature National Reserve.